2007
DOI: 10.1073/pnas.0705778104
|View full text |Cite
|
Sign up to set email alerts
|

Clonal interference in large populations

Abstract: Clonal interference, the competition between lineages arising from different beneficial mutations in an asexually reproducing population, is an important factor determining the tempo and mode of microbial adaptation. The standard theory of this phenomenon neglects the occurrence of multiple mutations as well as the correlation between loss by genetic drift and clonal competition, which is questionable in large populations. Working within the Wright-Fisher model with multiplicative fitness (no epistasis), we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
200
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(214 citation statements)
references
References 34 publications
11
200
1
Order By: Relevance
“…Although the average rate of fixations declines only modestly during the experiment, there is noticeable temporal variability as mutations often fix in “cohorts” of multiple linked mutations. These cohorts have been observed previously 1,29 and are expected in models of clonal interference 31,32 . However, they could also reflect transiently stable frequency-dependent interactions, as previously observed in Ara–1 29 .…”
Section: Dynamics and Fates Of New Mutationssupporting
confidence: 77%
“…Although the average rate of fixations declines only modestly during the experiment, there is noticeable temporal variability as mutations often fix in “cohorts” of multiple linked mutations. These cohorts have been observed previously 1,29 and are expected in models of clonal interference 31,32 . However, they could also reflect transiently stable frequency-dependent interactions, as previously observed in Ara–1 29 .…”
Section: Dynamics and Fates Of New Mutationssupporting
confidence: 77%
“…1B). Although theory (e.g., Rozen et al 2002;Park and Krug 2007) and data (e.g., Miralles et al 1999;De Visser and Rozen 2006) have previously demonstrated that competition between mutations in clonal lineages can lead to accelerated adaptation, ours is the first evidence that competition from mutations in competitors that are initially lower in fitness also influences the fitness effect of mutations that fix. The results imply that the evolutionary history of populations is written not only by the winners but by the losers as well.…”
Section: Discussionmentioning
confidence: 84%
“…The value ν c = 1/[N ln(N )] is thus the scale for clonal interference [23,30] and for the small island effect [24]. In fact, one can solve the difference equation (2) exactly by writing it as a first order difference equation for…”
Section: Neutral Dynamics With Pure Demographic Stochasticity (Dmentioning
confidence: 99%